Performance of CardioCel in Cardiac Surgery: A Systematic Review. Issue 2 (March 2023) - Patukale, Aditya A.; Suna, Jessica; Anand, Abhishek; Betts, Kim S.; Karl, Tom R.; Venugopal, Prem; Marathe, Supreet P.; Alphonso, Nelson
A systematic review was performed for evaluation of the performance of CardioCel ® in cardiac surgery. The review included all studies published from January 2013 to December 2020. We conclude that CardioCel is a strong, flexible tissue substitute with good handling characteristics and a low incidence of thrombosis, aneurysm formation, infection, or structural degeneration. It can be used for a variety of intracardiac and extracardiac repairs of congenital heart defects in all age groups with good durability at mid-term follow-up. However, the use of CardioCel in certain positions requires caution. Information on the long-term performance of CardioCel is lacking.